Sistem Deteksi Kemurnian Minyak Goreng Dengan Menggunakan Metode Gelombang Ultrasonik - Asriawan Pasca Ramadhan; Abdul Ro’uf (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2021)
Bulk cooking oil is a food ingredient that is widely used by the public. The seller uses used bulk cooking oil to be mixed with new bulk cooking oil or even mixes it with harmful ingredients. Lab tests are needed to determine the quality of cooking oil, but the lab test requires a long time and can also damage the content of the cooking oil so it cannot be reused. The focus of this research is the creation of a system that can detect the purity of cooking oil by utilizing the wave velocity measurement method without damaging the shape and nature of the cooking oil.Wave velocity measurements are carried out by propagating ultrasonic waves on objects with a wave frequency of 40 kHz. The value of the duration of the wave propagation time at a distance of 19.4 cm is sampled and used for the calculation of wave velocity. The results of these wave velocity calculations are used to determine the purity level of cooking oil. Then the results of the purity level obtained were analyzed with an approach to the value of fluid viscosity. The results of the wave velocity values show that the waves propagate faster if the purity level of cooking oil is higher and produces a positive correlation with R2=0.9784. The results of the analysis conducted with the approach to fluid viscosity also showed a positive correlation with R2= 0.9999. The average wave velocity in pure bulk cooking oil is 1174.90 m/s.